2016
DOI: 10.1177/0011392115623602
|View full text |Cite
|
Sign up to set email alerts
|

Making femicide visible

Abstract: The sociological literature on femicide, compared to intimate partner and other forms of gender violence, is scarce. While feminist sociology has addressed the inaudibility of women, femicide remains invisible. Femicide rates are social facts worthy of sociological attention. Like suicide, femicide has to be defined and analysed according to type. The article postulates possible reasons for the invisibility of the phenomenon, such as the unpleasantness of the subject, scope, its conception as a radical feminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 22 publications
0
41
0
5
Order By: Relevance
“…El Salvador had the highest rate (10.2 per 100,000 women), and Brazil had an intermediate rate (1.1 per 100,000 women), compared to the other countries included in the survey 15 . Despite the problem's importance, studies on intentional homicides of women (and specifically on femicides) are still scarce in the literature 4,16 .…”
Section: Introductionmentioning
confidence: 99%
“…El Salvador had the highest rate (10.2 per 100,000 women), and Brazil had an intermediate rate (1.1 per 100,000 women), compared to the other countries included in the survey 15 . Despite the problem's importance, studies on intentional homicides of women (and specifically on femicides) are still scarce in the literature 4,16 .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note the absence of specific studies relating to femicide among migrant populations in the studies sampled, and it is suggested to raise awareness of and to make this phenomenon visible (Weil 2016b). Concomitantly, studies of gender violence among internally displaced people were also found lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Tendency "included the following statements: 1, 3, 16, 21, 22, 23, 28, 43,45,49,52,54, 60, 64, 76 and 77 of the test. Statements related to this element have had obviously a prevailing place over other statements as they carried the greatest weight in the aim of the present study.…”
Section: Anthropological Researches and Studies No 8 2018 131mentioning
confidence: 99%